Techniques of monetary control - Aschheim, Joseph (Baltimore, Johns Hopkins Press, 1961)
This book is a study of the scope and method of central banking in the framework of the contemporary monetary system of the United States. Also it is made up essentially a series of essays, each concerned with individual techniques of monetary control. The first chapter summarizes the conclusions of subsequent chapters, and explicates the general view of central banking.
includes index
Includes bibliographical references
usc 16/6/17
Loans
Keywords: Monetary policy; Currency question; Monetary controls; United States